A case of pubic osteomyelitis after implantation of an artificial urinary sphincter: A case report. Issue 1 (25th August 2021) - Kusakabe, Naohisa; Kitta, Takeya; Chiba, Hiroki; Higuchi, Madoka; Shinohara, Nobuo
Abstract: Case: We describe a rare case of pubic osteomyelitis secondary to implantation of an artificial urinary sphincter (AUS). A 49‐year‐old man developed total urinary incontinence due to spinal cord injury 23 years earlier. After AUS implantation, he became continent. Fourteen years later, incontinence suddenly recurred. Outcome: We planned to replace the dysfunctional AUS with a new one. We removed only the implanted control pump, leaving the urethral cuff at the bladder neck and pressure‐regulating balloon to reduce surgical invasiveness, and performed AUS reimplantation. A new urethral cuff was placed around the bulbar urethra. Postoperatively, antibiotics, placement of a drainage catheter, and removal of the new AUS were required due to device infection. However, the infection persisted and magnetic resonance imaging showed inflammatory changes at the symphysis pubis, so osteotomy was performed to control infection. One year postoperatively, no gait disturbance or recurrence of pubic osteomyelitis was identified. AUS reimplantation was again performed and the patient is now socially continent. Conclusions: We have reported a rare case of pubic osteomyelitis secondary to AUS implantation. Clinicians should suspect pubic osteomyelitis if infection persists.